Poverty as Social Discourse in Joko Anwar’s Nightmares and The Daydreams (2024) - Muhammad Nabil Nuriman; Ade Kusuma (International Journal of Social, Economic, and Business, 2026)
The series Joko Anwar’s Nightmares and The Daydreams goes beyond genre-based supernatural science fiction and horror by embedding a layered social commentary on poverty and structural inequality. Poverty in the series is depicted not simply as financial deprivation, but as a complex condition marked by vulnerability, constrained agency, unequal access to resources, and dependency shaped by social structures. This article investigates how poverty operates as social discourse by analyzing narrative patterns, cinematic representation, and authorial perspective within the series. The study applies a qualitative method using Teun A. Van Dijk’s Critical Discourse Analysis framework, focusing on the interrelated dimensions of text, social cognition, and social context. Data are drawn from dialogues, character arcs, visual settings, and filmic techniques, and are interpreted alongside public statements by the director and current Indonesian social issues such as job insecurity, unequal educational access, precarious housing, and domestic violence. The analysis indicates that poverty is consistently framed through images of spatial confinement, limited opportunity, asymmetrical power relations, and systemic constraints that reproduce hardship across characters’ lives. The director’s creative choices position entertainment as a vehicle for social reflection, although the symbolic and indirect mode of critique means the deeper social message is more readily recognized by critically literate viewers than by general audiences.